Tubeimuside I improves the efficacy of a therapeutic Fusobacterium nucleatum dendritic cell-based vaccine against colorectal cancer - Tong, Yanan; Lu, Guoxiu; Wang, Zhiguo; Hao, Shanhu; Zhang, Guoxu; Sun, Hongwu (Frontiers in Immunology, 2023)
Fusobacterium nucleatum (F. nucleatum) infection has been confirmed to be associated with the development, chemoresistance, and immune evasion of colorectal cancer (CRC). In this study, we developed a new dendritic cell (DC) vaccine to investigate the antitumor efficacy of CRC immunotherapy strategies. By mediating a specific mode of interaction between the bacteria, tumor, and host, we found a new plant-derived adjuvant, tubeimuside I (TBI), which simultaneously improved the DC vaccine efficacy and inhibited the F. nucleatum infection. Encapsulating TBI in a nanoemulsion greatly improved the drug efficacy and reduced the drug dosage and administration times. The nanoemulsion encapsulated TBI DC vaccine exhibited an excellent antibacterial and antitumor effect and improved the survival rate of CRC mice by inhibiting tumor development and progression. This study provides a potential strategy for developing a therapeutic DC-based vaccine against colorectal cancer and underlies the importance of further understanding the mechanism of CRC processes caused by F. nucleatum.